The Influence of Financial Distress, Earnings Management, and Financial Performance on Firm Value with Good Corporate Governance as a Moderating Variable - Pui Heling; Hexana Sri Lastanti (Eduvest - Journal of Universal Studies, 2024)
This study examines the influence of financial distress, earnings management, and profitability on firm value, with good corporate governance (institutional ownership) as a moderating variable. Focusing on infrastructure sector companies listed on the Indonesia Stock Exchange from 2019 to 2023, this research employs Tobin's Q to measure firm value, the Altman Z-Score for financial distress, the modified Jones model for earnings management, and Return on Assets (ROA) for profitability. The findings reveal that profitability positively and significantly affects firm value, while financial distress and earnings management show no significant impact. Additionally, institutional ownership does not moderate the effects of financial distress and earnings management on firm value, though it successfully moderates the relationship between profitability and firm value. These results underscore the importance of profitability and good corporate governance in enhancing firm value, with implications for investor decision-making and corporate strategy in Indonesia’s infrastructure sector.